Wage bargaining and employment revisited: separability and efficiency in collective bargaining - Claus-Jochen Haake; Thorsten Upmann; Papatya Duman (The Scandinavian Journal of Economics, 2023)
We analyse the two-dimensional Nash bargaining solution (NBS) by deploying the standard labour market negotiations model of McDonald and Solow. We show that the two-dimensional bargaining problem can be decomposed into two one-dimensional problems, such that the two solutions together replicate the solution of the two-dimensional problem if the NBS is applied. The axiom of “independence of irrelevant alternatives” is shown to be crucial for this type of decomposability. This result has significant implications for actual negotiations because it allows for the decomposition of a multi-dimensional bargaining problem into one-dimensional problems~–~and thus helps to facilitate real-world negotiations.
Keywords: 330; Efficient bargains; labour market negotiations; Nash bargaining solution; restricted bargaining games; sequential bargaining